Blockchain-based reporting protocols as a collective monitoring mechanism in DAOs - Saeed Banaeian Far; Seyed Mojtaba Hosseini Bamakan (Data Science and Management, 2022)
As a recent decentralized business model, Distributed Autonomous Organization (DAO) challenges the management paradigms of conventional organizations and represents the future of democracy-based systems. However, DAOs are facing challenges that can be divided into two categories, including policy-based and technical challenges. Detecting misbehaving nodes is a crucial challenge that is considered in both categories. Designing mechanisms to report malicious behaviors while maintaining anonymity is essential for the survival and efficiency of DAOs. In this paper, we clarify the problem, and introduce Blockchain-Based Anonymous Reporting (BBAR) as a collective monitoring mechanism in DAOs with its requirements and implementation methods.